Säkrare etablering av våroljeväxter med grund bearbetning på våren - Tornerhjelm, Hilding (SLU/Dept. of Soil and Environment, 2016)
Spring oilseed rape is an important break crop in cereal dominated crop rotations in Mälardalen. Also, it is one of few good preceding crops to winter wheat. Establishment of spring oilseed rape is perhaps the most critical moment in arable cropping, especially under dry conditions on clay soils. In conventional systems, drying of soil during spring often makes it difficult to obtain enough soil moisture within the seedbed base for small-seeded species which are to be planted shallow. For saving as much soil moisture as possible within the soil for germination of spring oil seed rape, an alternative to using conventional machinery with plowing, harrowing and sowing, is to leave the soil unaltered during fall and instead use shallow cultivation in spring.